I am one : a book of action - Verde, Susan; Reynolds, Peter H. (Peter Hamilton), 1961- (2020)
One child who wants to make a difference joins with another and, through a series of simple actions and others' help, succeeds in making the world a better place. Includes a mindfulness exercise and notes about the importance of taking one first step
Illustrations rendered in ink, gouache, watercolor, and tea
Keywords: Social action -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Picture books; Picture books